APPLICATION OF BLENDED LEARNING MODEL (ENRICED – VIRTUAL MODEL) TO IMPROVE STUDENT'S INDEPENDENCE AND LEARNING ACHIEVEMENT (Studies on Indonesian subjects Social Studies Student Program Class XI SMA NEGERI 2 LEBONG) - Hengki Kurniawan; Johanes Sapri (UNIB Press, 2019)
The research commonly used to apply blended learning to improve student independence and learning achievement. The research method used is a research method that is a mixed research method. Mixed Methods Research used qualitative and quantitative elements. Of the three types Mixed Methods Research used the Exploratory sequential, Which started of Action research brazes. PTK is carried out in several cycles untik the appropriate model is obtained. The result of the PTK class were tested in the experiment class and the control class. Implementing blended learning one that result of cycle 1 until cycle 3, applied at class XI IPS.1 SMA Country 2 Lebong Regencies as classroom action research. As class of experiment is braze XI IPS.2. and control class XI IPS.3. Based on the results of the research that has been conducted in three cycles, it is known that the teacher’s ability to apply the belnded learning model has increased during the implementation of the action. Independence and student learning chvievement in the classroom towards Indonesia Language lessons has increased. It points out that learning model implement blended learning can improve students’s independence and learning achievement on learning material, although yhe increase obtained is not as good as expected but still on significant category. That thing regarded by factors as ability of teachers, student characteristic, environmentally, and patterned thinking factor. This research also produced a generic blended learning model, which means that this learning model can be applied to other schools that have the same characteristics as the experimental class in this study